Structure and antimicrobial activity of platypus 'intermediate' defensin‐like peptide. Issue 9 (30th March 2014) - Torres, Allan M.; Bansal, Paramjit; Koh, Jennifer M.S.; Pagès, Guilhem; Wu, Ming J.; Kuchel, Philip W.
Abstract : The three‐dimensional structure of a chemically synthesized peptide that we have called 'intermediate' defensin‐like peptide (Int‐DLP), from the platypus genome, was determined by nuclear magnetic resonance (NMR) spectroscopy; and its antimicrobial activity was investigated. The overall structural fold of Int‐DLP was similar to that of the DLPs and β‐defensins, however the presence of a third antiparallel β‐strand makes its structure more similar to the β‐defensins than the DLPs. Int‐DLP displayed potent antimicrobial activity against Staphylococcus aureus and Pseudomonas aeruginosa . The four arginine residues at the N ‐terminus of Int‐DLP did not affect the overall fold, but were important for its antimicrobial potency. Abstract : Three‐dimensional structure and antimicrobial activity of Int‐DLP were investigated. Structural fold of Int‐DLP was similar to that of the DLPs and β‐defensins. Int‐DLP was potent against S. aureus and P. aeruginosa bacteria. The 4 arginine residues at the N ‐terminus are important for its antimicrobial potency.